Sengketa Hukum Perjanjian Nominee Antara WNA dan WNI dalam Pengelolaan Tanah (Studi Putusan No. 259/pdt.G/2020/PN. Gin) - Nurcahya, Delviana Arsya (Peneliti.net, 2024)
This study aims to determine the legal consequences of nominee agreements between Indonesian citizens and foreigners in the practice of buying and selling freehold land. In this study, this journal used a normative type of research. The results of this study show the validity of the nominee agreement is an agreement made by foreigners and Indonesian citizens in carrying out legal actions, namely carrying out buying and selling activities on land objects in Indonesian territory. By borrowing the name of an Indonesian citizen, henceforth the Indonesian citizen takes legal action in the process of land sale and purchase transactions based on statutory provisions and then registers at the defense office in accordance with the ownership rights to the land listed on behalf of Indonesian citizens. Based on article 9 paragraph (1) of the UUPA only Indonesian citizens can have a full relationship with earth, water, and space and furthermore, in paragraph (2) states that every Indonesian citizen, both men and women have the opportunity to obtain a right to land and to benefit from the results, both for themselves and their families. Although the UUPA does not expressly regulate the nominee agreement, article 9 can be used as a basis for determining the validity of land ownership by foreigners in Indonesia, so that the nominee agreement is null and void.